MATHEMATICAL AND EXPERIMENTAL SIMULATION OF CARBON OXIDES AND EXCESS HEAT PROPAGATION IN GAS-AIR INDOOR ENVIRONMENT - Besarion C. Meskhi; Evgeny I. Maslov; Arkady N. Solovyev; Yury I. Bulygin; Denis A. Koronchik (Advanced Engineering Research)
Results of the mathematical and experimental simulation of the distribution of carbon monoxide and excess heat in the air of the garage premises are presented. Fields of air movement, carbon oxide concentration and temperature indoor comparable to the experimental data have been obtained on the ground of the theoretical and experimental method.